Long-term effectiveness of zoster vaccine live for postherpetic neuralgia prevention. Issue 36 (23rd August 2019) - Klein, Nicola P.; Bartlett, Joan; Fireman, Bruce; Marks, Morgan A.; Hansen, John; Lewis, Edwin; Aukes, Laurie; Saddier, Patricia
Abstract: Background: Postherpetic neuralgia (PHN) occurs in 5–30% of individuals with herpes zoster (HZ) and is characterized by long-lasting pain. Zoster vaccine live (ZVL) is licensed for people 50 years and older to prevent HZ and PHN. This study evaluated vaccine effectiveness (VE) of ZVL against PHN. Methods: We conducted an open cohort study within Kaiser Permanente Northern California with continuous accrual of people as they became age-eligible for ZVL. We defined PHN using a PHN diagnosis between 90 and 365 days after an incident episode of HZ. We estimated VE against PHN using Cox regression with a calendar timeline stratified by year of birth and adjusted for sex, race, influenza vaccination, outpatient visit frequency, comorbidities, and immune compromise status. Results: From 2007 to 2016, 1·5 million people entered the study population and 33% received ZVL. During 7·6 million person-years of follow-up, there were 62, 205 HZ cases, 4150 (6·7%) of which went on to develop PHN. Overall VE for PHN was 64·8% (95% CI 61·3, 68). VE was 82·8% (95% CI 77·6, 86·7) during the first year after vaccination, 58·3% (95% CI 50.1, 65.2) during the third year, and then waned more gradually to 48·7% (95% CI 30·2, 62·3) during the eighth year. VE in persons vaccinated when aged 80 years or older was similar to VE in younger vaccinees. VE in persons vaccinated when immune compromised was similar to VE in immune competent. Conclusions: Overall, ZVL was 65% effective against PHN. It was effective in all age groups and provided moderate protection through 8 years.